ANALISIS PERSEPSI STUART HALL TERHADAP MASYARAKAT AWAM MEMAKNAI MENIKAH DALAM HADIS NABI MUHAMMAD SAW - Mustofa, Ach Dimyati; Na’im, Muhammad Fathan (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
It is sunnatullah to marry. Islam emphasizes that Istatha'ah denotes inner manhood. Istatha'ah in the hadith means ability in all things, both the power to overcome and diminish the emotional turbulence within itself. Stuart Hall's social media message theory, or technique field study, was applied by the researcher. Among the ways the people in Tha'ah village relate to the custom of marriage is when a daughter follows her parent's wishes to get married in order to have a good child, and when a parent gives up their rights and obligations to an unmarried male at the age of 25, it's as if they are released from their obligations. 1) How people embrace the idea of marriage in the prophet's hadiths is the main area of study ? 2) What elements of society acceptability have influenced it ? 3) What effects does societal acceptance have ? An istatha 'ah is largely accepted by the public with a simple reading response.